(untitled) (Journal of Medicine, 2011)
Background: Rabies has been the subject of fear ever since the disease was recognized. Worldwide the number of deaths annually, due to rabies, is estimated to be between 35,000 to 50,000 approximately Rabies continues to be a major public health problem in Bangladesh killing an estimated 2000 people annually and 100,000 people receive post-exposure treatment in the country. In this regard the post-exposure treatment of animal bite cases is of prime importance. Materials and Methods: Communicable disease control(CDC) of, Directorate General of Health Services (DGHS) took the noble initiative to establish the national rabies elimination programme 2010 with an comprehensive approach of care for human and control of rabid animal. An expert group meeting for strategic plan and finalizing the guidelines for prevention and control of rabies cases was held in 2010, under CDC of DGHS to bring out uniformity in post-exposure treatment practices. . The participants in the meeting included practitioners managing anti-rabies clinics, laboratory medicine practitioners, policy makers, public health experts from both public and private sector. The guideline, which emerged out of consensus of expert groups, is summarized in this paper. Results: Until recently the Nervous Tissue Vaccine (NTV) was the mainstay for post-exposure prophylaxis in Bangladesh. As per WHO recommendations, the production and use of this reactogenic vaccine should be gradually phased out from our country. Modern, safe and effective anti-rabies Cell Culture Vaccines (CCVs) will be used for post-exposure prophylaxis in public sectors. The limitation is the high cost of this vaccine and also the cost and unavailability of Anti Rabies Immunoglobulin. WHO recommended the use of intra-dermal (ID) route of application of CCVs. Considering the recommendations of experts, results of clinical trials and international experience, experts of Bangladesh recommends ID regimen phase wise. In first phase, only Dhaka Infectious Disease Hospital will serve as Anti-rabies centre for ID regimen. After its successful implementation, ID regimen will spread out to Division and then to District level hospitals. National experts suggested and recommended the use of cost-effective vaccination schedules such as abbreviated multisite IM Zagreb protocol (4 dose, 3 visits) and updated Thai Red Cross (TRC) intradermal regimen(2-2-2-0-2) to phase out NTV and to make available modern rabies vaccine in public sector. Conclusion: This guideline will be extremely useful for the country to make rational use of modern rabies vaccine and phase out NTV by 2011. The guideline will be of immense use for better management of animal bite cases and availability and affordability of modern rabies vaccine will be of great help for physician to manage appropriately for preventing the deadly disease rabies. DOI: http://dx.doi.org/10.3329/jom.v12i2.7691 JOM 2011; 12(2): 153-159